2013
DOI: 10.1021/jf303739n
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Denaturation of Pea Globulins (Pisum sativum L.)—Molecular Interactions Leading to Heat-Induced Protein Aggregation

Abstract: The heat-induced denaturation and aggregation of mixed pea globulins (8%, w/w) were investigated using differential scanning calorimetry (DSC), SDS-PAGE, and size-exclusion chromatography (SEC-HPLC). DSC data showed that the pea proteins denaturation temperature (T(d)) was heating-rate dependent. The T(d) value decreased by about 4 °C by lowering the heating rate from 10 to 5 °C/min. The SDS-PAGE analysis revealed that protein denaturation upon heating at 90 °C was mainly governed by noncovalent interaction. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
82
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(96 citation statements)
references
References 36 publications
13
82
1
Order By: Relevance
“…Previous works have also shown that heat treatment of cowpea protein isolate at 70°C and 90°C (Peyrano et al, 2016) or whey proteins at 72°C and 140°C (Patel, Singh, Anema, & Creamer, 2004) did not produce changes in the polypeptide patterns after SDS-ME PAGE analysis. However, some of the proteins extracted by the SDS-ME buffer were too large to enter the gel as shown by the band at the origin (top of gel), which corroborates the data from native-PAGE and is consistent with previous reports (Chihi, Mession, Sok, & Saurel, 2016;Mession, Sok, Assifaoui, & Saurel, 2013;Shand et al, 2007).…”
Section: Polyacrylamide Gel Electrophoresissupporting
confidence: 91%
“…Previous works have also shown that heat treatment of cowpea protein isolate at 70°C and 90°C (Peyrano et al, 2016) or whey proteins at 72°C and 140°C (Patel, Singh, Anema, & Creamer, 2004) did not produce changes in the polypeptide patterns after SDS-ME PAGE analysis. However, some of the proteins extracted by the SDS-ME buffer were too large to enter the gel as shown by the band at the origin (top of gel), which corroborates the data from native-PAGE and is consistent with previous reports (Chihi, Mession, Sok, & Saurel, 2016;Mession, Sok, Assifaoui, & Saurel, 2013;Shand et al, 2007).…”
Section: Polyacrylamide Gel Electrophoresissupporting
confidence: 91%
“…Only a few studies on the differential scanning calorimetry (DSC) analysis of almost dry soy and pea proteins have been reported . In contrast, the literature on the thermal behavior of protein solutions and highly hydrated proteins is quite huge . However, the behavior at different moisture contents is very different, and information on the dry state cannot be extracted from that in solution.…”
Section: Introductionmentioning
confidence: 99%
“…20,24,25 In contrast, the literature on the thermal behavior of protein solutions and highly hydrated proteins is quite huge. [26][27][28][29][30][31][32][33][34][35][36] However, the behavior at different moisture contents is very different, and information on the dry state cannot be extracted from that in solution. On the contrary, in order to extend the actual knowledge on protein processing, it is very important to investigate in detail the thermal behavior of proteins at low moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…Using differential scanning calorimetry (DSC), a measure of the net difference between protein denaturation (endothermic process) and aggregation (exothermic process) occurring during heating, the main peaks for soluble leaf proteins were found to be 0.5, 0.8, and 1.8/100 g protein‐clarified alfalfa juice at 70, 68 and 65 °C, respectively. Besides these variations, RuBisCo shows a low denaturation temperature when compared to animal‐derived protein isolates such as egg protein and whey ( T d of 72 and 78 °C, respectively), and plant proteins such as soy ( T d of 73–90 °C), pea ( T d of 82 °C), and lupin proteins (66–91 °C) (Martin et al, ; Mession, Sok, Assifaoui, & Saurel, ; Munialo et al, ). A low denaturation temperature confers to RuBisCo the ability to rapidly form a gel at low concentrations under heating.…”
Section: Gelationmentioning
confidence: 99%